Analysis in making decision of farmer to select bull frozen semen in Indonesia - Agustine, R.; Bintara, S.; Andarwati, S.; Muzayyanah, M. A. U.; Widi, T. S. M.; Putra, A. R. S. (Diponegoro University, 2019)
The research objectives was to analyze the farmer’s decision in selecting breed of bull frozen semen for Artificial Insemination (AI) and determine the factors influencing the decision. There were five bull frozen semen options which simulated in this research, such as Simmental, Limousine, Ongole Grade (Peranakan Ongole / PO), Brahman, and other option. ”Other” option was used if the farmer did not recognize what breed of frozen semen was inseminated to their cow. Farmers must choose only one option of bull frozen semen that suitable for their cow. This study was conducted by collecting data using questionaire from 400 beef cattle’s farmers in Central Java Province and Yogyakarta Province. Respondents were selected by multistage random sampling technique. Descriptive statistical analysis and multinomial logistic regression analysis was used in this study The results revealed that 42% of farmers were more interested in inseminating their cows with bull semen from Simmental, and 30.75% of farmers were more interested in Limousin. Other variables such as family member, AI’s cost, land ownership, cow breed which lastly being inseminated, geographical factor, and farmer’s knowledge about the inseminatorswere variables that determine farmer’s decision process.